The new mechanism of cognitive decline induced by hypertension: High homocysteine-mediated aberrant DNA methylation - Wan, Chong; Zong, Rui-Yi; Chen, Xing-Shu (Frontiers in Cardiovascular Medicine, 2022)
The prevalence and severity of hypertension-induced cognitive impairment increase with the prolonging of hypertension. The mechanisms of cognitive impairment induced by hypertension primarily include cerebral blood flow perfusion imbalance, white and gray matter injury with blood–brain barrier disruption, neuroinflammation and amyloid-beta deposition, genetic polymorphisms and variants, and instability of blood pressure. High homocysteine (HHcy) is an independent risk factor for hypertension that also increases the risk of developing early cognitive impairment. Hcy levels increase in patients with cognitive impairment induced by hypertension. This review summarizes a new mechanism whereby HHcy-mediated aberrant DNA methylation and exacerbate hypertension. It involves changes in Hcy-dependent DNA methylation products, such as methionine adenosyltransferase, DNA methyltransferases, S-adenosylmethionine, S-adenosylhomocysteine, and methylenetetrahydrofolate reductase (MTHFR). The mechanism also involves DNA methylation changes in the genes of hypertension patients, such as brain-derived neurotrophic factor, apolipoprotein E4, and estrogen receptor alpha, which contribute to learning, memory, and attention deficits. Previous studies have shown that methionine (Met) induces hypertension in mice. Our recent study showed that DNA hypermethylation leads to cognitive behavioral changes alongside oligodendroglial and/or myelin deficits in Met-induced mice. Taken together, these studies demonstrate that DNA methylation regulates cognitive dysfunction in patients with hypertension. A better understanding of the function and mechanism underlying the effect of Hcy-dependent DNA methylation on hypertension-induced cognitive impairment will be valuable for early diagnosis, interventions, and prevention of further cognitive defects induced by hypertension.